Unravelling the effects of exploitation on the size–structure of the intertidal topshell Phorcus sauciatus in harvested and non-harvested Atlantic regions - Sousa, Ricardo (2022)
Intertidal molluscs are keystone species often used as biological indicators of human-driven pertur bations. The increasing levels of harvesting pressure on these intertidal grazers, due to the expansion of human population on coastal areas, is known to affect negatively the exploited populations by altering population size–structure and decreasing abundances. A comparative study on the effect of harvest on the size–structure of Phorcus sauciatus populations was conducted according to the exploitation level, harvested and non-harvested, throughout the intertidal zone of mainland Portugal, Azores, Madeira, and the Canaries. The comparative analysis of the size–structure of 10,480 individuals of P. sauciatus showed that the largest individuals were recorded in the Azores and the smallest in Madeira. In harvested populations, P. sauciatus showed to be under greater harvesting pressure in the archipelago of Madeira, where the lowest mean size was observed. In the Canaries the harvesting is regulated whilst in the mainland Portugal the regulation is scarce. The Azores showed no harvesting pressure. Marine Protected Areas showed individuals with the highest mean sizes supporting their effectiveness in preserving the size–structure of this species, regardless the ecoregion and thus, the harvesting pressure. The present results highlight the importance of harvesting regulation of P. sauciatus in Madeira, as well as the implementation of management measures aiming at the sustainable exploitation and conservation of this species.